LIFE QUALITY INCREASING AND DYNAMICS OF COGNITIVE PROCESSES AS THE RESULT OF EDUCATION AT THE “THIRD AGE” - E V Belovol; Z V Boyko; I V Radysh; E Yu Shurupova (RUDN Journal of Psychology and Pedagogics, 2015)
Longitudinal data obtained in the study of the influence of education at the third age on cognitive functioning and psychological status of elderly persons is analyzed in the article. The project started in October 2014 and will continue until December 2016. All the participants (N=21) are non-working pensioners with higher non-psychological education; in the project they are studying in the program “Practical psychology”, the duration of education is 2.5 years. As a result of the training the participants have become more confident in the sphere of social relations, they have become more self-confident, the future has stopped to seem meaningless for them. The students have become more confident in their cognitive abilities, their indices of cognitive consciousness and life satisfaction have increased significantly. As a result of the conducted research, it was revealed that learning in elderly years influences significantly the psychological well-being of elderly students. The improvement of cognitive functioning by the end of the first semester (six months after the beginning) was revealed as well. It is assumed that the improvement of cognitive functioning is due to changes in neuronal structures, as more time is necessary for these qualitative and quantitative changes.